Republic of the Philippines Labor Market Review : Employment and Poverty - World Bank (World Bank, Washington, DC, 2016)
This study analyzes labor market performance in the Philippines from the perspective of workers’ welfare. It argues that pervasive in-work poverty is the main challenge facing labor policy. Poverty is primarily due to low earning capacity of the poor and to their limited access to regular and productive jobs. Behind these are the two interrelated root causes of in-work poverty - low education of the poor, and the scarcity of productive job opportunities. The labor market is segmented into good and bad jobs, with the poor working in the latter. They hold jobs that are informal, temporary or casual, and low-paid. Widespread informality means that the poor neither benefit from the minimum wage policy nor from employment protection legislation. They do not benefit from wage growth either, because their bargaining power is weak. Good jobs are so few, especially in rural areas, that even better educated workers are often forced to take unskilled jobs and work as low-paid laborers. The reduction of in-work poverty hinges on removing constraints to gainful employment in both supply side (better education and skills) and demand side (better jobs). It is critical that the young poor have improved access to quality education, and be equipped with skills required in the modern sector of the economy. But in parallel, better jobs need to be created, which can be attained from the growth of the formal and higher value added sector of the economy. The process of structural transformation should be supported by effective labor policy. Labor regulations need to be made simpler and more flexible to facilitate the reallocation of labor from less to more productive activities, and from informal to formal sector. Targeted training programs have the potential to address the problem of low skills among the poor workers, especially the young ones. Such programs should be developed on a pilot basis and expanded if proven to be cost-effective.